Review of thermal and non‐thermal based endovenous treatment: Our local experience. Issue 4 (2nd November 2020) - Au‐Yeung, Chung Ling Karen; Tse, On Ho Ronald; Pang, Yin Chun Skyi; Tang, Chung Ngai
Abstract: Background: Endovenous treatment for varicose veins has become increasingly popular over the last decade. Compared to conventional surgery, endovenous options promise lower wound infection rates, less pain and quicker return to normal activities. Treatment modalities can be divided into thermal (EVLT / RFA) or non‐thermal based (Cyanoacrylate glue / MOCA). Literature review has not shown much difference between the two branches of treatment, and there remains a paucity of local data, hence we decided to conduct our own study to investigate the question. Methods: A retrospective single centre study was performed by pooling data from the Hong Kong Health Authorities electronic patient database between March 2012 and July 2018. Patients who had the procedure done under local anaesthetics were then contacted by phone and interviewed regarding their peri‐operative pain. Results: The study included 223 patients, 155 patients underwent radiofrequency ablation (RFA) thermal treatment and 68 patients underwent VenaSeal (Cyanoacrylate glue) non‐thermal treatment. Patients were demographically similar in terms of age, comorbidities, severity of varicose vein disease. More patients with thermal treatments had their procedure performed under general anaesthesia (GA) or monitored anaesthetic care (MAC) as compared to non‐thermal treatments. Patients were followed up for an average of 2.4 years in the thermal group and 1.3 years in the non‐thermal group. Patients in the non‐thermal group reported less perioperative pain, but overall, there were minimal complications and recurrence in both treatment modalities. Conclusion: Both types of endovenous treatment seem equally effective with few complications. Future prospective studies can be performed to reduce study bias.